An Easy-to-Implement Protocol for Preparing Postnatal Ventral Mesencephalic Cultures - Lautenschläger, Janin; Mosharov, Eugene V.; Kanter, Ellen; Sulzer, David; Kaminski Schierle, Gabriele S. (Frontiers in Cellular Neuroscience, 2018)
Postnatally-derived cultures of ventral mesencephalic neurons offer several crucial advantages over embryonic ventral mesencephalic cultures, including a higher content of TH-positive cells and the ability to derive cells from the substantia nigra, which contains the neurons most vulnerable to Parkinson’s disease. On the other hand, these cultures are more challenging to produce consistently. Here, we provide an easy-to-implement protocol for culturing postnatal ventral mesencephalic cells from the substantia nigra (SN) and the ventral tegmental area (VTA) using commercially available media, dishes, and general lab equipment, avoiding extensive material and equipment purchases. The protocol can be completed in about 5 hours and provides ventral midbrain neuron (VM) cultures on cortex glia feeder layers in three weeks’ time. The protocol uses an optimized protease digestion, tissue storage in Hibernate A during dissection and purification of neurons on an OptiPrep density gradient.